Efektivitas Metode Bercerita Dalam Mengembangkan Kemampuan Bahasa, Menyimak, Dan Interaksi Sosial Anak Usia Dini - Ester Mega Rani Br Sinuhaji; Sonya Febiola Br Nadeak; Dhieta Naiya A. Pasaribu; Fauzi Kurniawan; Jubaidah Hasibuan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language development is one of the important aspects of early childhood education. One of the methods that can be used to stimulate children's language development is the storytelling method. This research aims to analyse the application of storytelling methods and the use of learning media in the family environment as non-formal education. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research results show that the storytelling method supported by visual media such as picture story books and figure pictures can increase children's involvement in learning, enrich vocabulary, and improve children's communication skills. Learning takes place interactively between parents and children so as to create a fun learning atmosphere and in accordance with the stage of early childhood development.